Case Report: Blood single-cell analysis of a IVB high-grade serous ovarian cancer patient presenting a favorable prognosis - Wolańska, Martyna; Sieczczyński, Michał; Pastuszak, Krzysztof; Samelak-Czajka, Anna; Jackowiak, Paulina; Bednarz-Knoll, Natalia; Łapińska-Szumczyk, Sylwia; Klasa-Mazurkiewicz, Dagmara; Żaczek, Anna J.; Supernat, Anna (Frontiers in Oncology, 2025)
BackgroundHigh-grade serous ovarian cancer (HGSOC) diagnosed at stage IVB typically carries a poor prognosis. Here, we describe a rare case of with an exceptional and sustained response to therapy. To explore potential drivers of this favorable outcome, we combined clinical evaluation with molecular profiling of liquid biopsy samples.MethodsWe employed a multi-platform liquid biopsy approach in peripheral blood samples collected preoperatively. Bulk RNA sequencing was performed on platelet RNA, while single-cell RNA sequencing (scRNA-seq) profiled peripheral blood mononuclear cells (PBMCs). Additionally, circulating tumor cells were identified using imaging flow cytometry (imFC).ResultsSingle-cell transcriptomic analysis identified two candidate CTCs (Circulating Tumor Cells): one with an epithelial phenotype and another with a hybrid epithelial–mesenchymal (EMT) phenotype. The EMT CTC showed upregulation of IL12A, genes involved in the mTOR pathway (RPTOR, RICTOR, MTOR), and DNA repair, while the epithelial CTC expressed high levels of VEGFA. ImFC-based assay identified one putative mesenchymal-like CTC. Platelet RNA analysis revealed downregulation of ribosomal genes and upregulation of genes related to cytoskeletal remodeling and adhesion. ANGPT1 was downregulated, while AKT1 were upregulated, putatively indicating mTOR pathway activation. Glycolytic enzymes PKM and PGK1 were strongly upregulated, and reduced expression of DDIT4, HIF1A, CSF2RA, and CSF3R suggested altered stress and cytokine signaling.ConclusionThis integrative molecular and phenotypic profiling of blood-derived components identified potentially distinct molecular signatures, such as overexpression of IL12, ANGPT1 downregulation and HIF1A downregulation, in the literature described as linked to the patient’s beneficial prognosis. These findings suggest that advanced liquid biopsy techniques may provide complementary insights into prognostic biomarkers and therapeutic targets in HGSOC.